2022
DOI: 10.1080/21655979.2022.2065952
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine methyltransferase KIAA1429 elevates colorectal cancer aerobic glycolysis via HK2-dependent manner

Abstract: Emerging evidence has emphasized the critical roles played by N 6 -methyladenosine RNA (m 6 A) modification in colorectal carcinoma (CRC) initiation and progression. However, the roles and mechanism of m 6 A and KIAA1429 in CRC progression require further clarification. Here, our research aimed to investigate the functions of KIAA1429 in CRC tumorigenesis. Results indicated that KIAA1429 up-regulation closely correlated to the poor prognosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…GLUT1, a member of the GLUT family, the glucose transporter is an important protein that regulates intracellular glycolytic flux (29). Li et al (30) demonstrated that downregulation of HK-2-mediated glycolysis can inhibit the malignant progression of colorectal cancer. PDHK1 catalyzes glucose phosphorylation and inactivates PDH, the key enzyme for pyruvate to enter the citric acid cycle.…”
Section: Discussionmentioning
confidence: 99%
“…GLUT1, a member of the GLUT family, the glucose transporter is an important protein that regulates intracellular glycolytic flux (29). Li et al (30) demonstrated that downregulation of HK-2-mediated glycolysis can inhibit the malignant progression of colorectal cancer. PDHK1 catalyzes glucose phosphorylation and inactivates PDH, the key enzyme for pyruvate to enter the citric acid cycle.…”
Section: Discussionmentioning
confidence: 99%
“… Li et al (2022) studied the role of KIAA1429 in CRC. The results showed that KIAA1429 upregulation was closely related to poor prognosis of CRC patients.…”
Section: Survey Methodologymentioning
confidence: 99%
“…In vivo experiment on the BALB/c nude mice injected HCT116 cells with or without LINRIS knockdown observes that LINRIS knockdown suppresses the growth of CRC tumors and glycolysis mediated by IGF2BP2–MYC axis 355 . Emerging evidence indicates that the m 6 A methyltransferase KIAA1429 promotes aerobic glycolysis by upregulating HK2 expression 356 . Moreover, the m 6 A writer YTHDF2 degrades circ_0003215 to suppress signaling via the miR‐663b/discs large MAGUK scaffold protein 4 (DLG4)/G6PD axis and subsequently upregulate PPP and enhance the malignant phenotypes of CRC 357 .…”
Section: Rna Methylation and Cancer Metabolismmentioning
confidence: 99%